And then the roof caved in : how Wall Street's greed and stupidity brought capitalism to its knees - Faber, David, 1964- (Hoboken, N.J. : John Wiley & Sons, 2009)
Explains the events of the previous seven years that planted the seeds for the worst economic crisis since the Great Depression beginning in 2001, when the Federal Reserve embarked on an unprecedented effort to help the economy recover from the attacks of 9/11 by sending interest rates to all time lows.
Prologue: "on the verge" -- Bubble to bubble. Greenspan's shock and awe. Houses built on cow dung -- Home sweet home. Opening doors. An industry is born. Subprime returns -- The subprime machine. From delivering pizza to delivering mortgages. Living the dream. Diving into deep trouble -- Eyes wide shut. A warning unheeded. A dream no more -- The great enabler. Fannie Mae and Freddie Mac hit the scene. Fannie and Freddie get a timeout. Wall Street takes over. A tsunami of mortgages. From ownit to out of it. Back from the grave -- Complicity. Moody's the money maker. Repeat customers -- The securitization from hell. The making of a CDO. Tough to kill. Turning "crap into triple-A". From CDS to CDO. Insanity sets in -- Narvik and me. CDOs : an American export. The truth revealed--but does it matter? -- Mortgaging Merrill's future. Climbing out of poverty. A strong start. The secret weapon. Raking it in. Taking big risks -- A house of cards. Digging for gold. Building a case. The investment of a lifetime -- And then the roof caved in. The wheels coming off. The call. A crisis begins. The CDO blues. Light's out -- Epilogue.
Includes index.
Keywords: Real estate investment -- United States; Financial crises -- United States; Foreclosure -- United States